Effects of Newtonian Heating and Inclined Magnetic Field on Two Dimensional Flow of a Casson Fluid over a Stretching Sheet - Abid, Hussanan; Mohd Zuki, Salleh; Khan, Ilyas (Basha Research Corporation, Woodlands, Singapore, 2016)

(untitled)
It is known that the Navier-Stokes equations cannot describe the behaviour of fluids having high molecular weights. Due to the variety of such fluids it is very difficult to suggest a single constitutive equation which can describe the properties of all non-Newtonian fluids. Therefore many models of non-Newtonian fluids have been proposed. In this study, the steady two dimensional heat and mass transfer flow of a non-Newtonian Casson fluid over a linear stretching sheet in presence of an inclined magnetic field and radiation effects are considered. The sheet is subjected to Newtonian heating as well as convective boundary conditions. The governing partial differential equations are transformed to nonlinear ordinary differential equation by using similarity transformation. The solutions of these simplified coupled nonlinear equations are calculated using an analytical technique. The effects of various parameters on velocity, temperature and concentration profiles are presented through graphs and discussed.